Scheduling real-time fork-join structures in cluster computing. (3rd January 2006) - Ammar, Reda; Alhamdan, Abdulrahman
Scheduling a large number of high performance computing applications on cluster computing environment is a complex task especially in real-time systems. Efficient scheduling strategies are critically important for achieving a good performance. A cluster scheduler should adequately manage the cluster resources. In this paper, we present an algorithm for scheduling real-time applications represented as parallel task graphs on a cluster. We utilise the available processing power on each processor to maximise the degree of parallelism while satisfying the required tasks' deadlines. The algorithm reduces the communication cost among tasks and the possibility of processing power fragmentation.